Tradisi Islami dalam Kearifan Lokal: Praktik Budaya dan Adat Istiadat di Komunitas Pedesaan - Hiptraspa, Zepri; Saputri, Dea Novis (Islamic Extension Guidance Study Program (BPI) of the Faculty of Da'wah and Communication, 2024)
Abstract: Cultural heritage in the context of Islamic-based rural communities faces significant challenges due to modernization and social change. This article discusses strategies for balancing cultural conservation and adaptation in maintaining the sustainability of cultural heritage while adapting to changing times. An inclusive approach that combines local wisdom with modern aspects is crucial in caring for cultural heritage. Education that integrates religious values with contemporary learning and engages young people in activities that respect traditional values is needed. Additionally, the importance of building community awareness and involvement in caring for their cultural heritage is emphasized, with support from governments, cultural institutions and non-governmental organizations. The balance between cultural conservation and adaptation requires a holistic approach that combines traditional values with current developments. Through deeper understanding and a balanced approach, the cultural heritage and identity of Islamic-based rural communities can continue to live and develop in changing times.Abstrak: Warisan budaya dalam konteks masyarakat pedesaan berbasis Islam menghadapi tantangan signifikan akibat modernisasi dan perubahan sosial. Artikel ini membahas strategi keseimbangan antara konservasi budaya dan adaptasi dalam menjaga keberlanjutan warisan budaya sambil menyesuaikan dengan perubahan zaman. Pendekatan inklusif yang memadukan kearifan lokal dengan aspek modern menjadi krusial dalam merawat warisan budaya. Pendidikan yang mengintegrasikan nilai-nilai agama dengan pembelajaran kontemporer dan melibatkan generasi muda dalam aktivitas yang menghormati nilai-nilai tradisional diperlukan. Selain itu, pentingnya membangun kesadaran masyarakat dan keterlibatan dalam merawat warisan budaya mereka ditekankan, dengan dukungan dari pemerintah, lembaga budaya, dan organisasi non-pemerintah. Keseimbangan antara konservasi budaya dan adaptasi membutuhkan pendekatan holistik yang memadukan nilai-nilai tradisional dengan perkembangan zaman. Melalui pemahaman yang lebih dalam dan pendekatan yang berimbang, warisan budaya dan identitas masyarakat pedesaan berbasis Islam dapat terus hidup dan berkembang dalam perubahan zaman.